2022
DOI: 10.3390/biomedicines10030598
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein to Albumin Ratio as Prognostic Marker in Locally Advanced Non-Small Cell Lung Cancer Treated with Chemoradiotherapy

Abstract: Despite the implementation of consolidative immune checkpoint inhibition after definitive chemoradiotherapy (CRT), the prognosis for locally advanced non-small-cell lung cancer (NSCLC) remains poor. We assessed the impact of the C-reactive protein (CRP) to albumin ratio (CAR) as an inflammation-based prognostic score in patients with locally advanced NSCLC treated with CRT. We retrospectively identified and analyzed 52 patients with primary unresectable NSCLC (UICC Stage III) treated with definitive/neoadjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…And CAR is an easily available and independent prognostic marker in locally advanced Non-Small Cell Lung Cancer after CRT. 36 It is worth noting that these parameters are being reported for the first time on T2DM in patients with APTB.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…And CAR is an easily available and independent prognostic marker in locally advanced Non-Small Cell Lung Cancer after CRT. 36 It is worth noting that these parameters are being reported for the first time on T2DM in patients with APTB.…”
Section: Discussionmentioning
confidence: 92%
“…Non-Small Cell Lung Cancer after CRT. 36 It is worth noting that these parameters are being reported for the first time on T2DM in patients with APTB.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been successfully used as a prognostic factor for several malignant tumors. 37 , 38 In the field of HCC, studies have also shown that AFP combined with CRP can be used to predict the prognosis of HCC. 39 More importantly, Overexpressed CRP has more significant prognostic significance for patients with AFP negative.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of evidence has proven that the systemic inflammation and nutritional status are significantly associated with the incidence, disease progression, therapy and prognosis of cancer patients (5)(6)(7)(8)(9). In the last 10 years, some indexes reflecting the systemic inflammation and nutritional status of the body based on peripheral blood indicators were described and reported to be related to the prognosis of NSCLC patients such as the Creactive protein to albumin ratio (CAR) (10), albumin to globulin ratio (AGR) (11), and systemic inflammation response index (SII) (12). However, all these indexes are continuous variables and it is hard to define the normal or abnormal levels of individual patients.…”
Section: Introductionmentioning
confidence: 99%